Training Peer Support Workers in Mental Health Care: A Mixed Methods Study in Central Catalonia - Prat Vigué, Gemma; Cano Prieto, Ivan; del Río Sáez, Ruben; Vilanova Masana, Rut; Simó Algado, Salvador (Frontiers in Psychiatry, 2022)
Introduction A mental health peer support program was implemented at two reference institutions in Central Catalonia. The program culturally and contextually adapted successful international projects by training people with experience of mental health problems and ensuring their employment in multidisciplinary health care teams. This study explores the influence of peer interventions in mental health on the three groups of participants: peer support workers, service users, and mental health professionals. Methods A mixed observational method design included pre-, inter-, and post-experimental components and a qualitative description of the impact. The triangulation of the qualitative and quantitative findings showed its coherence and facilitated the understanding of the results. Outcomes and measures were as follows: self-stigma (Self-Stigma Questionnaire); life satisfaction (Scale of Satisfaction with Life); participation in relevant activities (Engagement in Meaningful Activities Survey); personal recovery (Scale-revised Recovery Assessment); occupational performance (Canadian Occupational Performance Measure); and attitudes toward mental illness (Community Attitudes toward Mental Illness). Results The program showed beneficial effects on peer support workers' (PSW) perceptions of occupational performance, specifically on the ability to find work (p = 0.038), work as a peer support worker (p = 0.016), give to the community (p = 0.011), and satisfaction in the ability to find work (p = 0.031). The assessment made by the three groups of participants was very positive: the PSWs showed an increase in self-esteem and a feeling of usefulness; users of the service described the experience as a source of hope and optimism in their recovery process; and professionals described the program as a positive step in their professional growth. Discussion The peer-to-peer strategy is a source of hope in the personal recovery process, providing meaning to life for the PSWs while providing an extra source of support to service users in their process of personal recovery. The results offer us lines of improvement for future implementations. PSW's final emphasis has us reflecting on improvements to enhance their own wellness in mental health care services. The findings show the importance of working on life projects and their impact on the recovery process.